Rancang Bangun Sistem Monitoring Gas CH4 dan CO2 Berbasis Internet of Things Studi Kasus TPST Bantar Gebang - Yulianto, Moh. Hendrik; Ferdiansyah, Ervan; Wastumirad, Adi Widiatmoko (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The Bantar Gebang Integrated Waste Treatment Site (TPST) is one of Indonesia's largest final disposal sites. The increasing generation of waste daily can cause methane (CH4) and carbon dioxide (CO2) emissions. Methane and carbon dioxide are greenhouse gases that can cause global warminag and endanger respiratory health at specific concentrations. Therefore, the authors created an IoT-based CH4 and CO2 gas monitoring system using the ESP32 as a microcontroller, the MQ-4 sensor to measure CH4, and the MG-811 sensor to measure CO2. The tool's design is simple and portable, with a 20x4 LCD, and the Blynk website can store data via an SD card. After testing, the tool can operate properly, and the results of CH4 and CO2 gas concentrations at the Bantar Gebang TPST location are around 2.01 ppm and 419.89 ppm with regular status.